SWINE CYSTICERCOSIS SEROPREVALENCE IN WAMENA, PAPUA REGION - Lingga, Alvionita Alexther; Swacita, Ida Bagus Ngurah; Suada, I Ketut (Buletin Veteriner Udayana, 2020)
Cysticercosis is a zoonotic disease caused by the larvae of Taenia solium which can affect human and animal health. Papua is one of the endemic areas of cysticercosis in Indonesia. This study aim was to determine the seroprevalence of swine cysticercosis in the region of Wamena, Papua. A total of a hundred and eleven swine serum samples collected from the region was then tested by using Enzyme Linked Immunosorbent Assay (ELISA). The results showed that the seroprevalence of cysticercosis in swine samples was 39.64% (44/111). It can be concluded that the seroprevalence of cysticercosis in swine of the region Wamena, Papua is realtively high. Therefore, it needs to design the disease control and eradicate program by relevant agencies in the region of Wamena, Papua.